Analysis and Design of a High Power Density Full-Ceramic 900 V DC-Link Capacitor for a 550 kVA Electric Vehicle Drive Inverter - Cittanti, Davide; Stella, Fausto; Vico, Enrico; Liu, Chaohui; Shen, Jinliang; Xiu, Guidong; Bojoi, Radu (2022 International Power Electronics Conference (IPEC-Himeji 2022- ECCE Asia), 2022)
The drive inverter is a crucial component of an electric vehicle (EV) powertrain, being responsible for the DC/AC power conversion between the battery and the electric motor. The increasing demand for lower weight and higher conversion efficiency is opening new challenges, encouraging the adoption of new technologies (e.g., wide bandgap semiconductor devices). In particular, the DC-link capacitor typically represents the bulkiest inverter component and poses a strict limitation to the achievable converter power density, therefore it is subject to strong pressure for improvement. In this context, novel ceramic capacitor technologies promise superior performance with respect to well established film-based solutions, featuring both higher specific capacitance and higher RMS current capability. Therefore, this paper focuses on the analysis, sizing and design of a full-ceramic 900 V DC-link capacitor for next-generation EV drive inverters, including a comparative assessment with a state-of-the-art film-based solution. For verification purposes, a DC-link prototype for a SiC MOSFET 550 kVA 25 kHz drive inverter is realized, demonstrating superior power density (i.e., ≈ 6.6 times smaller and ≈ 3.6 times lighter than a corresponding film-based solution). Furthermore, electrical and thermal measurements are performed on a ceramic capacitor sample, successfully supporting the DC-link sizing and design.